Analisis Dampak Pergantian Menteri Keuangan Terhadap Kinerja Indeks Harga Saham Gabungan (IHSG) - Iqbal Ananda; Melissa Rosalina; Riki Rahmansyah; Khalif Fadillah (Annusfy : Journal of Multidisciplinary Research, 2026)
This study aims to analyze the impact of the replacement of the Minister of Finance on the performance of the Jakarta Composite Index (JCI). Using the event study methodology, this study examines abnormal returns and trading volume activity within an 11-day period (D-5 to D+5) surrounding the announcement. The results reveal significant differences in impact. Sri Mulyani's re-inauguration triggered positive abnormal returns, reflecting market optimism (a positive surprise) driven by her credibility and track record among investors. Conversely, the appointment of Purbaya Yudhi Sadewa was followed by negative abnormal returns and high volatility, indicating a wait-and-see attitude and market uncertainty regarding the profile and competence of the new Minister of Finance in managing fiscal policy. These results confirm that market response is not solely determined by the official change event, but rather by the individual's credibility, performance track record, and the surrounding economic-political situation